Peran Teknologi Live Streaming dalam Pembentukan Identitas Sosial Mahasiswa Kewirausahaan di Direktorat Inovasi dan Inkubator Bisnis - Mutia Mawardah; Afifah Afrah Amatullah; Susan Dian Purnamasari (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
Live streaming has developed into a real-time communication medium that functions not only for commercial transactions but also as a space for self-expression and social interaction among young people. This study aims to describe the role of live streaming technology in shaping the social identity of Generation Z entrepreneurship students who participate in the business incubation program at the Directorate of Innovation and Business Incubator of Universitas Bina Darma. This research employs a qualitative approach with data collected through in-depth interviews, participatory observation, and Likert-scale questionnaires administered to 46 respondents who actively engage in live streaming. The data were analyzed thematically by referring to live streaming aspects (social presence, interactivity, engagement experience, entertainment value, and community involvement) and social identity indicators proposed by Michael A. Hogg (categorization, identification, social comparison, prototype, and depersonalization). The findings show that live streaming is perceived as an interaction in real live,” creating a warm and enjoyable atmosphere that enables respondents to remain focused to the point of losing track of time, thereby strengthening social presence and their sense of being accepted by viewers. Respondents feel proud to be part of the entrepreneurship group, adjust themselves to group norms, and see the group as part of their self-identity, indicating that the processes of categorization, identification, and depersonalization are taking place. This study concludes that live streaming serves as a digital arena that facilitates the formation and reinforcement of the social identity of entrepreneurship students, although the generalizability of the findings remains limited by the specific context and relatively small number of respondents.